Social Media Use, Professionalism, and Professional Identity Among Medical Students and Early-Career Health Care Graduates in Sudan: Cross-Sectional Survey Study - Fatima Elbasri Abuelgasim Mohammed; Enas Osama Hassan Omer; Ammar Elgadi; Ola Rashid Eltayeb Mamoun; Mohamed Shawgi Yassin Alsayed; Saad Elsayed; Ragheda Gamal Abdelrafi Musaad; Salma Sleak Alam; Mohamed Adam; Bayadir Adam Mohamed Adam; Sara Isam Eldin Ibrahim Elshafie; Mohanad Mustafa Mohamed Elamin; et al. (Online Journal of Public Health Informatics, 2026)
Abstract Background Social media has become deeply embedded in medical training, yet its influence on professionalism and the developing professional identity of medical students and early-career doctors remains insufficiently understood, particularly in non-Western contexts. Objective This study aimed to assess social media usage patterns, attitudes toward digital professionalism, related behaviors and experiences, and perceived benefits and risks among medical students and early-career health care graduates in Sudan, and to identify demographic and behavioral factors associated with key online behaviors and outcomes. Methods A cross-sectional online survey was conducted from June 2025 to August 2025 among 432 medical students, interns, early graduates, and residents in Sudan, recruited through convenience sampling. A structured, self-administered questionnaire developed specifically for this study assessed social media usage patterns, attitudes toward digital professionalism, related behaviors and experiences, and perceived benefits and risks. Descriptive statistics, chi-square tests, and multivariable logistic regression were performed using R software (version 4.4.2; R Foundation for Statistical Computing). Results Of the 432 participants, 226 (52.3%) were female participants, and 343 (79.4%) spent at least 3 hours daily on social media. Attitudes toward digital professionalism were generally positive: 225 (52.1%) participants agreed or strongly agreed that their online presence reflects their professional identity, and 390 (90.3%) considered maintaining a professional image is important. Nearly half of the participants (n=199, 46.1%) had modified or removed posts for professional reasons. The most reported benefits were access to updated medical knowledge (n=321, 74.3%) and career development (n=260, 60.2%), while common concerns involved misinformation (n=287, 66.4%), negative public perception (n=199, 46.1%), and confidentiality breaches (n=198, 45.8%). Female participants were more likely to report heavy daily use of 5 hours or more (109/226, 48.2% vs 70/206, 33.9%; P =.004). In multivariable analysis, male sex (odds ratio 2.12, 95% CI 1.36‐3.33; P